Ensemble recursive feature elimination-based ensemble classification for medical diagnosis - Ramanathan, Thirumalaimuthu Thirumalaiappan; Hossen, Md. Jakir; Al Mamun, Abdullah; Raja, Joseph Emerson (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The application of data mining techniques for the extraction of patterns from medical datasets is useful in the prediction of various diseases from the data of patients. An appropriate feature selection method is required for the medical datasets to give better results for the medical data mining process. In data preprocessing, feature selection is an important process that finds the most relevant features from the dataset. Considering all features of the medical dataset without using any feature selection process may sometimes lead to inaccurate results. Most of the medical datasets contain meaningless data that are not relevant to the data mining process. These data can be eliminated through the feature selection process. This paper presents an integration of an ensemble feature selection approach and an ensemble classification approach through a classifier called the ensemble recursive feature elimination-based ensemble classifier (ERFE-EC) for the classification of medical data. Four different medical datasets were used for testing the ERFE-EC method, which showed promising results.